PENGELOLAAN KAWASAN WISATA TERINTEGRASI DI KABUPATEN PONOROGO DENGAN PENDEKATAN CITY MARKETING - Bambang Kusbandrijo; Endro Tjahjono; Achluddin Ibnu Rochim (DIA: Jurnal Administrasi Publik, 2018)
Ponorogo Regency has the potential of tourism, including natural tourism, religious tourism and cultural tourism. The tourism sector has not been explored optimally so it has not become a tourist destination. This study answers two fundamental problems, namely the first to describe the tourism potential and the implementation of the development that has been carried out and secondly to develop a management model for Ponorogo tourist destinations in order to achieve development goals as a tourism area capable of increasing the PAD and economy of the Ponorogo community. Qualitative methods are used in research, primary and secondary data sources. Speakers were the Ponorogo Tourism service apparatus, cultural and tourism activists, NGOs. Field data results are interpreted, researchers interpret data by reviewing symptoms based on their perspective, comparing with previous studies. Research Results 1) Ponorogo has tourism potential, both natural, cultural, religious, culinary and cultural arts, creative economy. Tourism development in Ponorogo has not been optimal due to limited socialization and communication, infrastructure to tourist destinations is inadequate. The synergy between stakeholders has not yet been established so that tourism potential has not been optimal in providing economic impact to the community and increasing PAD. 2) The tourism development model certainly starts from the mapping of potential and management of development in an integrated and mutually reinforcing manner between tourism potentials. Tourism development needs to support a legal umbrella in the form of a Regional Regulation. Tourism development is carried out collaboratively by all parties so that all parties are jointly responsible for achieving success. All parties contribute according to the position and authority attached to high integrity and commitment